Existence in Meinongianism and Necessitism: A Merely Verbal Dispute - Conde Borrego, Violeta (Revista de Filosofía, 2026)
On the one hand, according to Meinongianism, there are two types of objects: those that exist and those that do not (which subsist). Moreover, among the objects that subsist, there is a special class of entities that are ‘beyond being’ (Nichtsein), such as impossible objects and fictional objects. On the other hand, according to necessitism, there are two types of objects: those that S-exist and those that L-exist. Furthermore, there is a third category of objects that do not L-exist, as their intended terms fail to refer—such as impossible objects and fictional objects.In this discussion, I will argue that the dispute between the Meinongianist and the Necessitist regarding the significance of existence is merely verbal and that both frameworks ultimately endorse a three-category ontology.
Keywords: existence; meinongianism; necessitism; merely verbal dispute